Adherence to antiretroviral treatment and associated factors among people living with HIV and AIDS in Kapilvastu district, Nepal - Shrestha, Neelam; Vaidya, Gemorina; Kumar Shah, Sudhir; Priyanka, Jyoti; Shrestha, Rubina; Thapa Sanwani, Kusum (Journal of Chitwan Medical College, 2025)
Introduction: Human immunodeficiency virus (HIV) is a public health problem. This study aimed to assess the adherence to antiretroviral therapy (ART) and associated factors among people living with HIV and acquired immunodeficiency syndrome (AIDS) in Kapilvastu district of Nepal. Method: A community-based cross-sectional study was conducted from Dec 2023 to Mar 2024, involving adult HIV positive patients in Kapilvastu district, Nepal. Participants were selected using a convenience sampling technique. Data were collected using face to face interviews from consented patients ≥18 years of age and on ART for at least 6 months. Patients who were mentally unfit and severely debilitated were excluded. Sociodemographic variables and adherence questionnaires based on Adult AIDS Clinical Trial Group were used. Ethical approval (UCMS/IRC/009/23) was taken from Universal College of Medical Sciences, Bhairahawa, Nepal. Data analysis was done using SPSS 20. Descriptive statistics, Chi-square tests and binary logistic regression were utilised. The level of significance was set at a p≤0.05. Result: The overall ART treatment adherence was 172(83.9%) among 205 patients. Alcohol consumption, thought of stopping ART treatment, reasons for not disclosing HIV status and means of reaching ART centre were found to be significantly associated with ART treatment adherence. Conclusion: This study highlighted a non-adherence rate of 16.1% to ART in HIV and AIDS patients, which remains an issue for treatment resistance and escalating morbidity and mortality.